2012
DOI: 10.1002/ange.201205596
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Coupling of ortho‐Alkynylanilines with Terminal Alkynes Under Aerobic Conditions: Efficient Synthesis of 2,3‐Disubstituted 3‐Alkynylindoles

Abstract: Zwei Nucleophile, eine Dreifachbindung: Unter aeroben Bedingungen liefert die Palladium‐katalysierte direkte Kupplung von o‐Alkinylanilinen mit terminalen Alkinen die 2,3‐disubstituierten 3‐Alkinylindole 3 in guten bis ausgezeichneten Ausbeuten. Die Zwischenstufe A wurde charakterisiert, und eine Retro‐Aminopalladierung von B wurde zum ersten Mal beobachtet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…To gain insight into the mechanism, a series of control experiments were performed. [6,11,14] In a set of two parallel experiments, we found that reaction of Pd(OAc) 2 with 1 a at room temperature afforded A cleanly, while reaction of Pd(OAc) 2 with 2 a directly afforded the cyclic dimer. (1), Scheme 3].…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…To gain insight into the mechanism, a series of control experiments were performed. [6,11,14] In a set of two parallel experiments, we found that reaction of Pd(OAc) 2 with 1 a at room temperature afforded A cleanly, while reaction of Pd(OAc) 2 with 2 a directly afforded the cyclic dimer. (1), Scheme 3].…”
Section: Methodsmentioning
confidence: 97%
“…(1), Scheme 3]. [6,11,14] In a set of two parallel experiments, we found that reaction of Pd(OAc) 2 with 1 a at room temperature afforded A cleanly, while reaction of Pd(OAc) 2 with 2 a directly afforded the cyclic dimer. [15] These results clearly showed that Pd(OAc) 2 can catalyze the cyclization of both 1 and 2.…”
Section: Scheme 2 Cyclizative Cross-coupling Reaction Of O-alkynylanmentioning
confidence: 99%
“…Firstly, addition of Pd(OAc) 2 (0.8 equiv) to the mixture of 1 a (1.0 equiv) and 2 a (1.0 equiv) in [D 6 ]DMSO at room temperature gave, after 5 minutes, the intermediate A as the only product in about 56 % yield [Eq. (1), Scheme ] 6. 11, 14 In a set of two parallel experiments, we found that reaction of Pd(OAc) 2 with 1 a at room temperature afforded A cleanly, while reaction of Pd(OAc) 2 with 2 a directly afforded the cyclic dimer 15.…”
Section: Methodsmentioning
confidence: 98%
“…Although conceptually appealing, the practical execution of the cyclizative cross‐coupling between 1 and 2 is challenging. Indeed, both 1 and 2 have a high propensity to undergo the cyclization leading to cyclic monomers5 and recently, their cyclizative dimerizations2h, 6 have also been reported. In addition, while the o ‐alkynylanilines 1 are known to undergo only the 5‐ endo ‐dig cyclization,7 the o ‐alkynylbenzamides 2 can cyclize by both the 5‐ exo ‐dig and the 6‐ endo ‐dig modes using either an oxygen or nitrogen center as an internal nucleophile 8–10.…”
Section: Methodsmentioning
confidence: 99%
“…To our surprise, ac yclization-alkynylation domino process was unprecedented. [15,16] Recently,w ed eveloped cyclization-alkynylation domino reactions to access functionalized furans [17] and indoles [18] based Scheme1.Ta rgetedt etracenes:f lexible synthesis and hole mobility prediction.…”
Section: Synthesis Of Heterotetracenesmentioning
confidence: 99%